HAS PLAGIARISM SPREAD TO PHYSICS PRACTICUM REPORTS? - Nugroho Prasetya Adi; Tika Erna Putri; Wahyu Waskito Aji; Aulia Silvia Anandita; Muhammad Zaini; Sri Jumini (Physics Education Study Program, Faculty of Education and Teacher Training, UNSIQ, 2026)
In the field of education, the phenomenon of plagiarism is not a new issue. Plagiarism is often regarded as a trivial violation of academic ethical norms and is even considered commonplace by many individuals within academic environments. In essence, plagiarism constitutes an academic offense and is a criminal act categorized as a copyright infringement, as regulated under Law No. 28 of 2014 concerning Copyright. This study employed a quantitative research design with a survey approach aimed at identifying the phenomenon of plagiarism in the preparation of physics practicum reports. The sample consisted of 91 students who had participated in physics practicums, including both basic physics and electronics. The sampling technique used was purposive sampling, taking into account specific characteristics aligned with the objectives of the study. The instrument used for data collection was an online questionnaire consisting of several questions distributed through Google Forms. The questionnaire was analyzed for validity and reliability, where validity testing was conducted using the Product Moment method and reliability testing was performed using Cronbach’s Alpha. Data analysis in this study employed descriptive statistical techniques. The results showed that 30 students, or 33%, admitted to committing plagiarism in the preparation of physics practicum reports, while 61 students, or 67%, had never engaged in plagiarism in preparing such reports. The forms of plagiarism committed included the use of assistance applications, copying practicum reports from senior students, and manipulating practicum data. The reasons students engaged in plagiarism in preparing physics practicum reports included limited references, lack of time to prepare the reports, and insufficient skills in composing physics practicum reports properly